2009
DOI: 10.1073/pnas.0900043106
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically driven programmable liquid motion using resonance cavities

Abstract: Performance and utility of microfluidic systems are often overshadowed by the difficulties and costs associated with operation and control. As a step toward the development of a more efficient platform for microfluidic control, we present a distributed pressure generation scheme whereby independently tunable pressure sources can be simultaneously controlled by using a single acoustic source. We demonstrate how this scheme can be used to perform precise droplet positioning as well as merging, splitting, and sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…The possible applications for acoustic pumping technology extend into medical applications, for example, the insulin pump reported by Ma et al (2006), where the PZT was used in a Helmholtz cavity arrangement to deliver insulin into a silicon patch with surface machined hollow microneedles designed to painlessly puncture the skin. By applying this idea at far lower frequencies, well into the audible range at around 100 Hz, but in a set of resonance cavities external to the microfluidics device, each holding fluids to be delivered, Langelier et al (2009) were able to selectively pump these fluids through the device as shown in Fig. 11.…”
Section: Fig 8 (Color Online)mentioning
confidence: 99%
“…The possible applications for acoustic pumping technology extend into medical applications, for example, the insulin pump reported by Ma et al (2006), where the PZT was used in a Helmholtz cavity arrangement to deliver insulin into a silicon patch with surface machined hollow microneedles designed to painlessly puncture the skin. By applying this idea at far lower frequencies, well into the audible range at around 100 Hz, but in a set of resonance cavities external to the microfluidics device, each holding fluids to be delivered, Langelier et al (2009) were able to selectively pump these fluids through the device as shown in Fig. 11.…”
Section: Fig 8 (Color Online)mentioning
confidence: 99%
“…The fluid propulsion in microfluidic systems is performed using three different approaches: (i) mechanical methods -such as external syringe pumps, peristaltic pumps [74,64,30,86,58,31] and membrane pumps, (ii) using the electrokinetic properties of the fluids -such as in electro-osmotic pumps [97,67] and magnetohydrodynamic pumps [63,37,42,93] -and (iii) acoustic methods [60,73,96,95]. These fluid propulsion mechanisms have been developed only in recent years.…”
Section: Lab-on-a-chipmentioning
confidence: 99%
“…The most common pumping methods employed in microfluidics are gravity-driven and syringe-mediated pumping, of which the latter is more reliable. More elaborate pumping systems include 'Quake valves', 32 Braille actuation, 33,34 acoustics, 35 and most recently autonomous pumping regulation by embedded components. 36 The reproducibility and versatility of generation of temporal patterns is in large part determined by the pumping mechanisms implemented for conveying fluids through the microfluidic channels.…”
Section: Microfluidics To Enable Pulsatile Stimulation Of Cellsmentioning
confidence: 99%